An effective method and pathways of acrylonitrile degradation to acrylic acid through an alkaline hydrothermal system. Issue 13 (18th July 2017) - Dong, Wenjie; Peng, Boyu; Wang, Ke; Miao, Jia; Zhang, Wei; Zhang, Yalei; Shen, Zheng
ABSTRACT: Degradation of pollution for specific chemicals represents an optimal approach to high-strength wastewater treatment. One-pot selective conversion of acrylonitrile to acrylic acid in a hydrothermal system with NaOH as a catalyst was carried out. The influence factors were evaluated, including initial acrylonitrile concentration, reaction temperature, reaction time and amount of alkali. Experimental results showed that the highest yield of acrylic acid (55%) was obtained at the initial acrylonitrile concentration of 3 × 10 3 mg/L, 300°C for 90 s with 1.0 M NaOH. To determine the reaction path, intermediates analysis and calculation of carbon and nitrogen balance were carried out by means of HPLC, GC and TOC/TN methods. Two probable reaction pathways were proposed as follows: (1) Acrylonitrile was hydrolyzed into acrylamide, and acrylic acid was obtained via further hydrolysis. (2) Acrylonitrile was converted into 3-hydroxy-propionitrile via additive reaction, and this product was readily converted to 3-hydroxy-propionic acid through two steps of hydrolysis, followed by dehydration reaction to produce acrylic acid. This study offered not only an efficient method to transfer highly toxic pollutants into valuable chemical, but also a better understanding of hydrothermal alkali catalytic reaction.